Oral Clonidine in reduction of postoperative nausea and vomiting after laparoscopic cholecystectomy: A double blinded placebo controlled trial - Bhandari, Sandip; Basnet, Madindra; Shrestha, Gentle Sunder; Marhatta, Modh Nath (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: The common adverse effects of laparoscopic cholecystectomy include nausea and vomiting. Surgical pneumoperitoneum can stimulate vagal response and induce the release of various emetogenic substances such as 5-hydroxytryptamine and acetylcholine. We hypothesized that oral Clonidine administered preoperatively reduces the post operative nausea and vomiting following laparoscopic cholecystectomy. Methodology: In a randomized, double-blinded placebo controlled study, seventy patients undergoing laparoscopic cholecystectomy were assigned to receive either oral Pyridoxine (placebo) or oral Clonidine 200?g 20-30 minutes before conduction of general anaesthesia. We assessed post operative nausea and vomiting and compared its incidence following laparoscopic cholecystectomy with prophylactic use of oral Clonidine or placebo. We also found out the requirements of rescue antiemetic medication (Ondansetron and Promethazine) for post operative nausea and vomiting after prophylactic use of oral Clonidine or Placebo. Results: Three patients in Clonidine group and 12 patients in Placebo group vomited in first two hours. Likewise, 11 and 22 patients vomited in Clonidine and Placebo group over 24 hours respectively. In group Clonidine, 18 patients had nausea in first two hours and 20 patients had nausea over 24 hours. In group Placebo, 33 patients developed nausea in first two hours and over 24 hours. Ten patients in Clonidine group and 19 patients in Placebo group required Ondansetron as rescue antiemetics over 24 hours. Conclusion: Oral Clonidine given pre-operative to patients undergoing laparoscopic cholecystectomy decrease the incidence of post operative nausea and vomiting. Journal of Society of Anesthesiologists 2014 1(2): 76-79